Interactivity Strategies and Engagement in Universities’ Social Media Communication: Insights from Latin America, Europe, and the United States - Capriotti, Paul; Zeler, Ileana; Martínez-Reig, David (Cuadernos.info, 2024)
This article aims to analyse whether the interactivity strategies implemented by universities from Latin America, Europe, and the United States on their social networks, including their general approach and the communication resources applied in their posts, influences the degree of participation of their publics. A content analysis has been applied to analyse 90,241 posts on institutional profiles on X (formerly known as Twitter), Facebook and LinkedIn from 70 universities in these three regions. Results indicate that Latin American institutions do not have a distinctly different interactivity strategy from European and the US ones. The interaction rates achieved by universities are very low, in relation to other sectors and those recommended by experts. The interactivity strategy of the universities is not adequate enough since the communication approach of the university publications is highly informative in all social networks and the communication resources are mainly expository, although more and more they are combined with interactive resources. This research proposes a framework to measure and evaluate the interactivity strategy of organisations in social networks, identifying and analysing its key dimensions.